An institutional theory perspective on the role of project management associations for projectification of society: the case of Germany. Issue 8 (7th June 2022) - Wagner, Reinhard; Huemann, Martina; Radujković, Mladen
Abstract : Purpose: This paper aims to provide insights into the role of project management associations for the projectification of society from an institutional theory perspective. Design/methodology/approach: The paper is based on a mixed methods approach. It draws on the research propositions of a recently conducted qualitative study and builds on them by analyzing the empirical data of a quantitative case study. Findings: The results indicate that the projectification of society in Germany is well advanced and continues growing. The economy plays a leading role, which resonates with other sectors of society. The actions of project management associations have only an indirect influence on the projectification of society, which cultural–cognitive institutions are mediating. Both findings are novel compared to the literature. Practical implications: Taking an overall view of the findings, project management associations gain a better understanding of the projectification process and important guidance on their role. Social implications: The results offer all people interested intriguing insights into the contemporary phenomenon of the projectification of society, along with its current state and future evolution. Originality/value: The application of institutional theory to the projectification of society in the framework of this case study enables an in-depth analysis of the underlying social processes and interactions between the regulative, normative and cultural–cognitive activities of project management associations on the one hand, and institutions on the other hand, at the societal level. This opens up new and promising perspectives for further research.